ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Conventional rigid electronic components often suffer from mechanical mismatch with soft biological tissues, resulting in discomfort, unstable signals, and mechanical failure under repeated deformation. To address these challenges, we present a sprayable bio-inspired hydrogel (SOPB) synthesized from okra mucilage, polyvinyl alcohol, and borax, with NaCl incorporation to enhance ionic conductivity. This hydrogel shows strong adhesion, injectability, stretchability, transparency, self-healing capability, passive thermal regulation, conductivity, and antibacterial activity against Escherichia coli and Staphylococcus aureus-a rare combination of properties within a single material platform. Its porous, water-rich network promotes efficient ion transport, while its conductivity enables stable electrochemical signaling, making it highly suitable for biosensor applications. Remarkably, the hydrogel performed comparably to commercial electrodes in surface electromyography (sEMG) and electrocardiography (ECG) measurement using Shimmer3 device. We fabricated a low-cost, multilayered hydrogel-based device (OKPVD device) capable of monitoring various human motions (finger, knee, and wrist bending, as well as tapping and walking) and detecting different emotional states, such as different facial expressions. Beyond sensing, the hydrogel's adaptability underscores its potential for wearable bioelectronics and skin-friendly E-skindevices. This work presents a facile sprayable fabrication route that integrates biomedical engineering, soft electronics, and human-machine interfaces for healthcare and rehabilitation.